Melacak jejak politik persebaran islam antara Elit kerajaan Majapahit dan Wali Sanga: (Konsolidasi hukum islam di Jawa) Ke -2 - Ridwan, Nur Khalik (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2020)
Islamic law is applied in all places where Muslims are to apply the teachings of Islam from the Qur’an and sunnah, as well as the qaul-qaul of scholars in ijma and qiyas. Its application in each place is always related to the political law of power and the situation in which the region is located, as well as the existence of deliberations and political law of power between the scholars and rulers. Especially in Javanese society, this is clearly seen, how the aristocratic elite and scholars play a role, so that the political pattern of power law among Javanese Muslims has its dimensions because there is a local dialectic, prakrassa ulama and aristocratic elite. This article would like to see the political law of power carried out by scholars and aristocratic elites in Java in the early days, as a reflection for the development of the cultural Islamic movement in Java, while still referring to Islamic law which, within certain limits must be applied flexible, in addition to the question of elementary laws, such as prayer, fasting, and pilgrimage. Therefore, this article would like to trace: the politics of the spread of Islam in the application of Islamic law in Javanese society, the relationship of elite nobles and scholars who spread Islam in the early days, and the Islamic law culturally applied in Javanese society; and its relevance for the present.